Restoring African Drylands - Pasiecznik, N.; Reij, C. (2020)
ETFRN News 60 focuses on dryland restoration in the Sahel and the Greater Horn of Africa. It collates 36 articles from more than 100 contributors, including examples of remarkable increases in tree cover and improved agricultural yields over large areas of the Western Sahel, landscape restoration in Ethiopia, and examples from many other countries.